Cultural Ecosystem Services – Framework, Theories and Practices - Dłużewska, Anna (Problemy Ekorozwoju, 2016)
The article above is an attempt to present main issues of conceptual background and research practices for cultural ecosystem services, seen as an important part of sustainable development, for its practical implementation. The author begins with conceptual background of ecosystems services as whole, then goes to cultural ecosystem services conceptual background and finally to cultural ecosystem services research practice. The last part of the article gives an overview of participant disciplines (their methodologies and perspectives), main research topics, national/ geographical background of authors, and finally – main weaknesses of contemporary researches and main challenges for the future ones.